2012
DOI: 10.1080/13698575.2011.641523
|View full text |Cite
|
Sign up to set email alerts
|

Constructing sexual risk: ‘Chikan’, collapsing male authority and the emergence of women-only train carriages in Japan

Abstract: Women-only train carriages have been introduced in Japan as a response to widespread groping (chikan) by men. In August 2007, 155 young women completed a survey at a variety of locations in central Tokyo, mainly at the popular meeting places, Shinjuku and Shibuya. The survey involved face-to-face interviews conducted mainly by young female interviewers. The numbers involved are insufficient for rigorous statistical analysis and in this pilot study we were principally interested in further refining ideas and hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(27 citation statements)
references
References 15 publications
(7 reference statements)
2
24
0
Order By: Relevance
“…Reynolds 2016). There is emerging evidence that while some women may approve of these services, they may not use them, as has been found in Japan (Horii and Burgess 2012). Furthermore, the concept of women-only transport is considered problematic as it is seen to reinforce a message that women must be contained and segregated in order to protect them (Gekoski et al 2015, 10).…”
Section: Solutionsmentioning
confidence: 95%
See 1 more Smart Citation
“…Reynolds 2016). There is emerging evidence that while some women may approve of these services, they may not use them, as has been found in Japan (Horii and Burgess 2012). Furthermore, the concept of women-only transport is considered problematic as it is seen to reinforce a message that women must be contained and segregated in order to protect them (Gekoski et al 2015, 10).…”
Section: Solutionsmentioning
confidence: 95%
“…Sexual harassment on public transport appears to be primarily non-confrontational, although it often may include forms of confrontational harassment in the form of subtle groping, touching or leaning (Hsu 2011;Gekoski et al 2015). It usually occurs in closed-crowded spaces, where strangers take advantage of environmental conditions to harass (Hsu 2011;Horii and Burgess 2012;Madan and Nalla 2016). For example, Hirsch and Thompson (2011, 3) recount womens stories of standing in very crowded situations and being unsure if men were trying to take advantage of them.…”
Section: Introductionmentioning
confidence: 99%
“…Fear of using public transport may have multiple adverse effects on women including amongst victims of unwanted sexual behaviour: mental health problems (Horii & Burgess, 2012); agoraphobia (Fahmy et al, 2014); disturbed sleep, and nightmares (Battered Womens Support Services, 2014). Victims, and those who fear victimisation, may feel angry, disgusted (Jafarova et al, 2014), upset, anxious, humiliated (Fahmy et al, 2014), objectified, and frustrated (Dhillon & Bakaya, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Other surveys reveal that between 28 percent (Okabe, 2004) and 70 percent of women and girls (Anka et al 2001, Ishibashi, 2003 ) have experienced chikan. In a more rigorously reported study (high relevance/medium confidence) interviews with 155 young Tokyo based women in their 20s or under, found that 48 percent had been groped on a train (Horii & Burgess, 2012).…”
Section: Asiamentioning
confidence: 99%
“…The first two train cars are exclusively for women, disabled, and the elderly (Dunckel-Graglia 2013). Some cities have applied exclusive cars for women as a measure to decrease sexual harassment (Junior et al, 2017;Horii et al, 2012).…”
Section: Introductionmentioning
confidence: 99%